2002
DOI: 10.1183/09031936.02.00221602
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily tobramycin in the treatment of adult patients with cystic fibrosis

Abstract: Once-daily tobramycin in the treatment of adult patients with cystic fibrosis. A. Whitehead, S.P. Conway, C. Etherington, N.A. Caldwell, N. Setchfield, S. Bogle. #ERS Journals Ltd 2002. ABSTRACT: The aim of this study was to test the equivalence of once-and thrice-daily dosing with tobramycin by comparing efficacy and safety in adult patients with cystic fibrosis.Sixty adult patients with an acute respiratory exacerbation were randomized to receive either 10 mg?kg -1 tobramycin once-daily or 3.3 mg?kg -1 tobra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 30 publications
6
54
0
1
Order By: Relevance
“…6,7 Studies have shown that extended-interval (i.e., once daily) tobramycin is a safe and effective alternative to traditional (i.e., every 8 hours) tobramycin dosage. [14][15][16][17][18][19] The results of our survey are consistent with these findings that 80% of pediatric and 96% of adults centers reporting use of extended-interval tobramycin. The most frequently used initial dosage of tobramycin for extended-interval therapy in both adult and pediatric patients was 10 mg/kg per dose every 24 hours.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…6,7 Studies have shown that extended-interval (i.e., once daily) tobramycin is a safe and effective alternative to traditional (i.e., every 8 hours) tobramycin dosage. [14][15][16][17][18][19] The results of our survey are consistent with these findings that 80% of pediatric and 96% of adults centers reporting use of extended-interval tobramycin. The most frequently used initial dosage of tobramycin for extended-interval therapy in both adult and pediatric patients was 10 mg/kg per dose every 24 hours.…”
Section: Discussionsupporting
confidence: 89%
“…14,21,22 Most pediatric and adult survey respondents reported a goal C max that ranged between 20 and 40 mg/L, trough serum concentrations <1 mg/L, and AUC ranges of 70 to 125 mg*hr/L, which are consistent with literature recommendations. [14][15][16][17]19,[20][21][22] Follow-up monitoring of serum concentrations differed between pediatric and adult respondents. Pediatric respondents measured only trough concentrations every 7 days, whereas most adult respondents measured 2 random serum concentrations every 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…8 In light of the emergence of safety and efficacy data in the CF population, the Cystic Fibrosis Foundation deemed once-daily aminoglycoside dosing as acceptable for Pseudomonas aeruginosa (grade C recommendation) in its September 2009 pulmonary exacerbation guidelines. [9][10][11][12][13][14][15][16][17][18] A 2009 survey of United States pediatric CF centers and affiliate programs distributed after the publication of these guidelines reported the use of EID (with once-daily or twice-daily dosing) in the pediatric CF population to be 94%, a significant increase from previous reports. 19 While empiric evidence suggests the use of EID of aminoglycosides to be increasingly common in the United States CF population, the prevalence of EID use across United States adult CF centers as well as the dosing and monitoring practices associated with this regimen following publication of the CF pulmonary exacerbation guidelines remain to be elicited.…”
Section: Introductionmentioning
confidence: 65%
“…This likely reflects the availability of well-designed safety and efficacy studies and meta-analyses evaluating tobramycin EID in this population, and the lack of published research studies assessing the use of gentamicin and amikacin EID in those with CF. 10,11,[13][14][15][16][17][18] As in the pediatric CF population, empiric dosing of tobramycin was most commonly prescribed at 10 mg/kg/d. 19 This practice is consistent with the dose used in a large, randomized, controlled, noninferiority study published in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Piperacillin appears to be associated with febrile reactions in patients with CF 15 and should be avoided. Once daily tobramycin does appear to be effective in patients with CF, 16 but this conclusion is based on a small study and confirmation is required. Burkholderia cepacia is usually multiresistant but may be sensitive to chloramphenicol, cotrimoxazole, ceftazidime, temocillin, or meropenem.…”
Section: Management Of Massive Haemoptysismentioning
confidence: 99%